Concepts underlying continuity of care - the system of concepts described in ENV 13940a - François Mennerat; Nick Booth (Journal of Innovation in Health Informatics, 2002)
In 1998, the Technical Committee 'Health Informatics' (TC 251) of CEN (European Committee for Standardisation) set up a specific project team to address aspects of sharing patient-related information needed in the process of care, in order to support continuity of care, giving way to a European pre-standard, numbered ENV 13940. The authors were both members of that project team. The system of concepts and the terms defined in this European pre-standard are designed to support the management of healthcare-related information over time, and the delivery of relevant health care by different agents, encompassing primary care professionals and teams, healthcare funding organisations, managers, patients, secondary and tertiary healthcare providers, and community care teams. Beyond the terms used in the standard, which have no actual value outside the framework of the document itself, the goal is to establish a common conceptual framework for continuity of care across national, cultural and professional barriers. It is neither to define how the processes should be performed in a particular healthcare framework, nor to have any regulatory impact on the actual delivery of care. The European pre-standard does not address other aspects of health care, such as security, the specific management of professional acts and their life cycle, terminology and classification, nor the financing mechanism for healthcare delivery.